POLITIK TEOLOGIS: Konsep Pemikiran John Calvin tentang Pemerintahan dan Pelayanan untuk Menilai Masalah Korupsi di Nusa Tenggara Timur - Rona, Heber (LOKO KADA TUO: Jurnal Teologi Kontekstual dan oikumenis, 2025)
This article was written with the aim of reviewing the study of John Calvin's concept of political theology regarding the practical political perception of church officials and specifically state government. This research discussion paper was completed using qualitative research methods by examining the concept of Calvin's thought specifically on government and church services and specifically the state. Therefore, each data is specifically collected by reviewing any literature that is relevant to what is being discussed. This study simply shows that Calvin saw government from two parts, namely the government of the Church (spirituality). Second, from the perspective of the state government (outwardly). From these two views, factors emerge which are influential in carrying out political service practice and in terms of political service practice in state government positions, which then become more of an economic factor which is more politically beneficial for state government officials. This research study and discussion is more specifically aimed at state government officials so that they can reform their understanding of politics correctly and theologically in accordance with what Calvin meant about his political theology in government and ministry.